Inhabitable space control for the creation of healthy interactive spaces through emotional domotics - Navarro-Tuch, Sergio A.; Bustamante-Bello, M. Rogelio; Molina, Arturo; Izquierdo-Reyes, Javier; Avila-Vazquez, Roberto; Pablos-Hach, Jose Luis; Gutiérrez-Martínez, Yadira (International journal on interactive design and manufacturing, 2018)
In recent years, Mexico’s level of different physiological and mental negative states, such as stress have increased. This has among its consequences, low work production and social problems including the alarming numbers that nearly 43% of adults report high levels of stress. The increase of stress incidence in people aged 15–29 years, and the lack of stress relief measures have an important impact on a person’s physical, mental and emotional health. In order to diminish these negative effects different approaches can be implemented for example, the use of audiovisual stimulus to induce emotions [ 1 ]. In this work the emotional analysis through facial expression is implemented [ 2 , 3 ]. We propose the use of domotics to influence the user’s emotional state, creating an interactive space that reacts to the users emotions adapting to the most suitable scenario. The first experiments we conducted occurred in an industrial production simulator in which lights’ hue was varied in order to perceive the impact of such lights on the emotions reflected by the subject. The emotional impact was analyzed through the FACET TM module of the biometric platform iMotions TM . These experiments together with the experience of other investigators leaded to the design and construction of an experimental booth that let us experiment with other variables like humidity and temperature. The design of one of such experiments is presented in this work based on a stress profile. This experiment’s objective is to allow us to correlate the impact of the environmental variables over the emotional state reflected on subjects’ expressions in order to integrate it for a control loop. The final system has multiple potential applications, among them one is the implementation for the analysis of design prototypes of both products and architecture models.